Cellulose acetate metal-impregnated membranes for air separations. - El-Taki, Wassim. (University of Ottawa (Canada), 1995)
Polymeric membranes are widely used in the oxygen enrichment of air for medical purposes and in the preparation of nitrogen for use in blanketing applications. Membranes having both high selectivity and permeability are essential for these applications. In this work, several membranes were prepared by the phase inversion technique. Casting solutions containing cellulose acetate, EDTA and acetone were spread onto a backing material and gelled in iced water. The membranes were then subjected to several post-treatments such as annealing, silver impregnation and silver impregnation followed by reduction to silver metal. The effects of EDTA and film post-treatments were determined with respect to air permeability and oxygen concentration in the permeate. The porosity of the resulting membranes were determined using gas sorption techniques. The presence of EDTA in the casting solution increased the entrapment of silver within the membrane. The air permeability of the membrane and oxygen concentration of the permeate were individually normalized. An objective function was defined as the product of the normalized air permeability and the normalized oxygen concentration in the permeate. The objective function exhibited an optimum at the solubility limit of 2% EDTA in water. However, the excessive presence of EDTA reduced both membrane air permeability and oxygen separation. The presence of silver in the membrane caused the blockage of pores in the 30-100 A diameter range. The pore size distributions of the membranes, measured using gas sorption techniques, provided a good explanation for the observed air permeability and oxygen separation of the membranes.
Keywords: Engineering, Chemical.